Does Fiscal Transparency Explain Social Development in Brazilian States? - Welles Matias de Abreu; Ricardo Corrêa Gomes; Solange Alfinito (Revista Sociedade, Contabilidade e Gestão, 2015)
Comparative studies show significant results when compared with fiscal transparency social indicators in the framework of democratic processes. However, careful analysis of the consequences associated with fiscal transparency are still surprisingly scarce. The aim of this research is to verify the existence of relationship between fiscal transparency and local development in the Brazilian states. The theoretical framework is related to public budget, focusing on fiscal transparency, and social development. In addition, to control social development by groups of Brazilian regions, we use a dummy variable. Therefore, this paper contributes to find empirical evidence on the existence of directly proportional relationship between state fiscal transparency and local development in Brazil. Moreover, it is important to highlight that the regional issue is fundamental to explaining social development, which together with fiscal transparency should be consider essential for formulation and implementation of public policies focus on the reducing of poverty and inequality in Brazil. Therefore, we expect that his article collaborated with data and ideas in order to stimulate further studies related to the consequences of fiscal transparency, considering all government levels: state, municipality and federal.